Мigration processes and sustainable development: brief analysis ofkey linkages and gaps (International relations and international law Journal, 2016)
Migrationprocesses acquirea new shapein the context ofglobalization and sustainable development. The migration andsustainable developmentnexusis one of thedisputable issuesin contemporaryacademicmigration discourse. The key linkagesof these processesare seeninthe increasing role ofinternationalhuman rightsof migrants, the role ofremittancesfor the economy ofthe host countriesand the contribution of migrantsto the development ofthe recipient countries. All these elementsarean important part ofdefining themigration andsustainable development nexus. Analysis of the key linkagesof migrationand sustainable developmentis the most promisingin view ofa positive visionin which themigrationin the context of globalizationare seenas contributing to thedevelopment,and not asa whole range ofthreats and challenges, both in host countriesand inthe countries of origin. The weakness of the nexusis seenas key gaps that needto be rethinkingand fill out.
Keywords: sustainable development; international migration; remittances; the rights of migrants